Hoxa9 and Meis1 Are Key Targets for MLL-ENL-Mediated Cellular Immortalization - Zeisig, Bernd B. (American Society for Microbiology, 2004)
MLL fusion proteins are oncogenic transcription factors that are associated with aggressive lymphoid and myeloid leukemias. We constructed an inducible MLL fusion, MLL-ENL-ERtm, that rendered the transcriptional and transforming properties of MLL-ENL strictly dependent on the presence of 4-hydroxy-tamoxifen. MLL-ENL-ERtm-immortalized hematopoietic cells required 4-hydroxy-tamoxifen for continuous growth and differentiated terminally upon tamoxifen withdrawal. Microarray analysis performed on these conditionally transformed cells revealed Hoxa9 and Hoxa7 as well as the Hox coregulators Meis1 and Pbx3 among the targets upregulated by MLL-ENL-ERtm. Overexpression of the Hox repressor Bmi-1 inhibited the growth-transforming activity of MLL-ENL. Moreover, the enforced expression of Hoxa9 in combination with Meis1 was sufficient to substitute for MLL-ENL-ERtm function and to maintain a state of continuous proliferation and differentiation arrest. These results suggest that MLL fusion proteins impose a reversible block on myeloid differentiation through aberrant activation of a limited set of homeobox genes and Hox coregulators that are consistently expressed in MLL-associated leukemias.